Strategi Pengembangan Agroindustri Pepaya di Kabupaten Boyolali - Indreswari, Rysca; Paryanto, Edi; Adi, Raden Kunto; Dewanti, Rizki Puspita; Ningsih, Hardian; Yunindanova, Mercy Bientri; Agustina, Ana; Apriyanto, Dwi (Jurnal Social Economic of Agriculture, 2024)
Papaya agribusiness in Boyolali Regency has yet to develop optimally, focusing primarily on production, while the agroindustry (processing) aspect remains underdeveloped. The aim of this research is to formulate a strategy for the development of the papaya agroindustry. This study employs a descriptive qualitative and quantitative approach using a case study method, with data collection techniques including document review, observation, interviews, and focus group discussions (FGD) involving stakeholders at the district level. The collected data were analyzed using SWOT analysis. The research findings indicate that an aggressive agroindustry development strategy is essential. This strategy is highly beneficial as it leverages the strengths and opportunities available to support business growth. Key strategies to be implemented include scaling up the papaya agroindustry, diversifying products, enhancing entrepreneurial mindset and skills, and conducting intensive marketing of quality products by utilizing stakeholder networks. Furthermore, collaboration with modern retailers such as Alfamart, Indomart, Mitra Supermarkets, and Luwes in the Solo Raya area, as well as with the Boyolali Regency Local Brand Forum (FBL), is crucial. Additionally, partnerships with papaya processing technology service providers, such as LPK, the Industry and Trade Service, the MSME and Cooperative Service, relevant Ministries, and Universities, are recommended to support the development of the sector.